IS INPUT SUBSIDY STILL USEFUL FOR INDONESIAN AGRICULTURE? - Wirakusuma, Gilang (Jurnal Ekonomi dan Pembangunan, 2020)
Government policies in the form of input subsidies have become an essential instrument for improving the performance of the agricultural sector and overcoming the limitations of resources owned by farmers. However, there are still questions about how effective this policy can be in boosting agricultural performance. This study aims to examine the impact of channeling input subsidies on agricultural productivity. Using the 2014 Agricultural Census microdata, 26,079 rice farm households were included in the analysis. Propensity Score Matching (PSM) is used to examine the impact of input subsidies on agricultural productivity represented by the productivity of rice farming. PSM was chosen because it can overcome the selection bias that could potentially arise in the analysis process. The analysis showed that the PSM model succeeded in reducing bias and confirmed that input subsidies had a significant effect on the productivity of rice farming. Thus, the input subsidy policy is an important and relevant instructor to improve the performance of the agricultural sector.